BIODEGRADATION OF REACTIVE DYE REACTIVE VIOLET 5 BY BACTERIA ISOLATED FROM DYE CONTAMINATED SOIL - MALLIKARJUN C. BHEEMARADDI; SANTOSH PATIL; CHANNAPPA T. SHIVANNAVAR; SUBHASCHANDRA M. GADDAD (International Journal of Pharma and Bio Sciences, 2013)
The Pseudomonas aeruginosa GSM3 isolated from dye contaminated soil was able to degrade Reactive Violet 5 completely as a sole source of carbon (300 mgL−1) within 20 h under static condition. The organism exhibited good decolorization ability in the pH ranges from 5.0 to 9.0 and temperature from 30 to 40oC respectively. The optimum degradation was observed at 37oC and pH 7. The maximum concentration of Reactive Violet 5 (800 mgL−1) was degraded up to 58% within 68 h. The culture showed remarkable ability to decolorize repeated additions of dye, with decrease in time up to 10 h at fifth dye aliquots addition and also tolerate high salt concentration up to 6 gLâ”€1 NaCl. Contineous decrease in optical density at 558 nm on incubation, increased the colorless bacterial biomass and no change in color on changing pH of decolorized filterate depicted that decolorization was due to biodegradation. Thus, the isolate P. aeruginosa GSM3 could be good candidate organism for the biotreatment of textile industry effluents.